CLINICAL EFFECTIVENESS OF ECTOSAN APPLICATION AT SHEEP SCAB - Dovgyi, Yu. Yu.; Prus, P. M. (Scientific Progress & Innovations, 2020)
Sheep scab is an extremely spread disease, which is connected with favorable conditions for parasites on the skin of these animals and a large number of sheep kept together. Clinically, sheep scab is characterized by skin lesions in the form of alopecia with hair loss in chunks, itching, the development of papular and pus-tular dermatitis, allergic manifestations against the background of weight loss and symptoms of general in-toxication. Psoroptes ovis mites were detected during the studies, the intensity of infestation made up to 10 mites per 10 cm2 of skin. In hematological indicators, changes in the form of leukocytosis, eosinophilia, rod-shaped neutrophilia, lymphocytopenia and monocytosis were detected in diseased animals. This indicated the development of a systemic reactive inflammatory process in the body as a result of intoxication effect of the causative agent and allergic reaction of the animal on the pathogen with an attempt to block its antigens. The inhibiting of cellular immunity reactions was determined, as well as activation of the mononuclear phagocyte system as a natural process in fighting dermatozoonoses pathogens. Billirubinemia and increase in transaminase activity (AST, ALT) were significant biochemical parameters, which changed as a result of sheep scab. Such changes determine the development of reactive hepatitis and liver failure as a consequence of the pathogen toxic effect on the animal body. The using of “Ectosan” preparation to treat sheep scab re-sulted in disappearing of disease symptoms in 15 days (the effectiveness made 75–80 % on the 15th day and 100 % on the 30th day). Laboratory blood indices were stabilized to control values during the observation period, except for monocytosis and creatininemia. The latter indicators indicated the residual pathological processes as a result of the preparation’s effect on the animal body, which did not disappear during the ob-servation period. The dysfunction of the kidneys filtration capacity was also revealed, which was accompa-nied by an increase in the level of residual nitrogen in the blood serum, increasing sheep intoxication. Mon-ocytosis after the disease treatment evidenced that fighting skin inflammation was not completed during the month of the observation period.